Innovation in Information Technology: A Hybrid Systematic Literature Review and Bibliometric Analysis - Faezal Erlangga; Lukman Abdurrahman (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to provide an overview of the development and scope of research on Innovation in Information Technology through a hybrid approach combining Systematic Literature Review and bibliometric analysis. The study examines 121 articles selected from the Scopus database using the PRISMA 2020 framework. A bibliometric analysis was conducted using VOSviewer to identify publication trends, research distribution, and relationships among key keywords. The results indicate that research on Innovation in Information Technology remains relatively limited and is dominated by developed countries, with a primary focus on technological aspects and organizational contexts. These findings offer both theoretical and practical implications for advancing research and formulating sustainable information technology innovation strategies in the future.